ANALISIS MODEL MENTAL SISWA DALAM PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 8E PADA MATERI HIDROLISIS GARAM - Darmiyanti, Waskitarini; Rahmawati, Yuli; Kurniadewi, Fera; Ridwan, Achmad (Jurnal Riset Pendidikan Kimia (JRPK), 2017)
This study aims to analyse the students’ mental model of students in SMA 42 Jakarta in the implementation of Learning Cycle 8E learning model on salt hydrolysis learning. This research was conducted in first semester of 2016/2017 academic year. There are 36 students of year XI in MIPA 5 was involved in the study. This qualitative research was conducted with the data collection of writing-drawing technique, in-depth interviews, classroom observation, student journal reflective. The Miles and Huberman data analysis was employed with quality standards of data reduction, display data, and verification. Class observation conducted before and after the learning Cycle 8E was implemented for understanding, the characteristics of students and classroom learning environment. The interview technique was conducted to have deep understanding the students’ mental model. The result showed that the students developed understanding on the concept of hydrolysis reaction process and pH of salt solution which were generated categories of understanding, not understanding, and misconception. The three categories are seen from the four stages of the learning Cycle 8E which are explore, elaborate, extend, and explain. students’ understanding and mental model development are influenced by the learning environment and prior knowledge. This model also has developed students’ soft skills of empathy communication, critical thinking and collaboration skills. Keyword: Chemistry Education, Mental Model, Salt Hydrolysis, Learning Cycle 8E